The effect of copper fungicides on the rate of photosynthesis and the transpiration of hop plants - Pokorny, Jaroslav; Pulkrábek, Josef; Krofta, Karel; Ježek, Josef (Acta Agraria Debreceniensis, 2011)
The paper evaluates the effect of copper fungicide spraying on the rate of photosynthesis and transpiration of hops, the influence of spraying on the elemental copper content in the leaves and cones hop variety Agnus. Photosynthetic rate was measured by LC pro+ (infrared analyzer) in the Hop Research Institute Saaz in the field in some periods of 2008, 2009 and 2010. Dry cones and leaf samples (taken before and after application of copper fungicides) were analyzed in an accredited laboratory for elemental copper.